One new species of the genus Capnogryllacris Karny, 1937 (Orthoptera: Gryllacrididae) from China - Duan, Yue-Ting; Chen, Po-Wei; Shi, Fu-Ming (Zootaxa, 2023)
The paper reports a new species of the genus Capnogryllacris Karny, 1937 (Orthoptera: Gryllacrididae) from China, i.e. Capnogryllacris latilamargis sp. nov. The all specimens are deposited in the Museum of Hebei University, Baoding, China.